Afektywny wymiar powstańczej narracji wspomnieniowej (na przykładzie leksykalnych manifestacji radości w wywiadach z Archiwum Historii Mówionej Muzeum Powstania Warszawskiego) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article focuses on lexical updates of emotions from the group of joy present in the reminiscent narratives of the Warsaw Uprising witnesses and the determination of their role in shaping the image(s) of that event in collective memory. The research material comprises 3,400 accounts developed as part of the project entitled the Archive of Oral History of the Warsaw Uprising Museum. The analyses’ theoretical and methodological background constitutes the assumptions of memory linguistics and corpus linguistics. The research (both quantitative and qualitative research) on the affective dimension of memories in the form of direct descriptions of joy allows us to conclude that the witnesses often verbalize joy directly, this feeling is still alive and intense in their accounts, it is also aroused by similar events.What is also important is the coherence of the vision of the uprising in the minds of the uprising participants and in the narrative conducted by the institutional initiator of the memories – the Warsaw Uprising Museum.